1994
DOI: 10.1007/bf00005131
|View full text |Cite
|
Sign up to set email alerts
|

Diel and density-related changes in food consumption and prey selection by brook charr in a New Hampshire stream

Abstract: SynopsisWe report the results of a field study testing influences of both density and changes over the diel cycle on food consumption and prey selection by brook charr, Salvelinus fontinalis. Charr density in replicate 35 m long sections of a New Hampshire stream was adjusted to either medium or high levels (relative to natural densities) . Diets of charr and the availability of drifting prey were then sampled every four hours for 24 hours .There were no significant diel changes in the weight of prey consumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 41 publications
2
63
1
Order By: Relevance
“…For all months (except May 2004), no single scarabaeid species was ranked as the most important prey item, but the entire family ranked very high in both frequency of occurrence in brook trout stomachs and in mean energy provided per capture. As a family, guchi and Nakano 2001; Kawaguchi et al 2003), Alaskan (Wipfli 1997) and eastern United States streams (Forrester et al 1994;Utz and Hartman 2007;Sweka and Hartman, in press). However, few researchers have identified a specific family or species of terrestrial organism that provides a large amount of energy as consistently as do the scarabaeids in the Middle Fork River watershed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For all months (except May 2004), no single scarabaeid species was ranked as the most important prey item, but the entire family ranked very high in both frequency of occurrence in brook trout stomachs and in mean energy provided per capture. As a family, guchi and Nakano 2001; Kawaguchi et al 2003), Alaskan (Wipfli 1997) and eastern United States streams (Forrester et al 1994;Utz and Hartman 2007;Sweka and Hartman, in press). However, few researchers have identified a specific family or species of terrestrial organism that provides a large amount of energy as consistently as do the scarabaeids in the Middle Fork River watershed.…”
Section: Resultsmentioning
confidence: 99%
“…Besides Sweka (2003), we could locate only one other literature report of scarabaeids as important salmonid prey, and this was anecdotal (Ratcliffe and Ocampo 2002). Unfortunately, a typical approach in descriptive studies of salmonid diets has been to classify all terrestrial organisms into a single, broad category (Cada et al 1987;Forrester et al 1994;Bridcut and Giller 1995;Nakano et al 1999;Mookerji et al 2004). While we previously reported moderate terrestrial taxonomic analysis in a related study (Utz and Hartman 2007), the current study suggests that careful analysis of terrestrial taxonomic detail in fish diets reveals important ecological phenomena.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elliott 1965Elliott , 1967Elliott , 1970Elliott , 1973Sagar & Glova 1988). From spring until autumn, when stream salmonids are active (and potentially able to feed) throughout the diel cycle, most studies of wild fish have found peaks in feeding at dawn and/or dusk (when light intensities are not constraining and drift abundance is higher than the daytime level) but rather little and less selective foraging during the night itself (Elliott 1970(Elliott , 1973Jenkins, Feldmeth & Elliott 1970;Sagar & Glova 1988;Angradi & Griffith 1990;Riehle & Griffith 1993;Forrester, Chace & McCarthy 1994).…”
Section: Discussionmentioning
confidence: 99%